2002
DOI: 10.1159/000066148
|View full text |Cite
|
Sign up to set email alerts
|

Speech Loudness and Quality 12 Months after Intensive Voice Treatment (LSVT<sup>®</sup>) for Parkinson’s Disease: A Comparison with an Alternative Speech Treatment

Abstract: Thirty-five individuals with idiopathic Parkinson’s disease were enrolled in speech treatment. Twenty-two were enrolled in a high-effort phonatory-respiratory treatment program (Lee Silverman Voice Treatment, LSVT®) and 13 were enrolled in a high-effort respiratory treatment program (RET). Perceptual judgments of speech loudness and quality were made independently by 6 listeners on recordings of the ‘Rainbow Passage’. These recordings had been obtained just before treatment (pre) and at 12 months’ f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
51
0
17

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(71 citation statements)
references
References 28 publications
2
51
0
17
Order By: Relevance
“…Introduced by Ramig et al [14] in 1987, the LSVT program has been evaluated in numerous published investigations. LSVT is an intensive, high-effort treatment with focus on increasing phonatory effort, vocal fold adduction, and sensory perception of effort [15,16]. Treatment is delivered 4 times a week over 4 weeks.…”
Section: Introductionmentioning
confidence: 99%
“…Introduced by Ramig et al [14] in 1987, the LSVT program has been evaluated in numerous published investigations. LSVT is an intensive, high-effort treatment with focus on increasing phonatory effort, vocal fold adduction, and sensory perception of effort [15,16]. Treatment is delivered 4 times a week over 4 weeks.…”
Section: Introductionmentioning
confidence: 99%
“…19 Behavioral speech therapy, including intensive voice treatment, appears to be the most effective type of speech intervention in the early and moderate stage of PD at present. 15,20 However, the requisite physical visit to the clinic for treatment is difficult and burdensome for many PD patients, 21 and the reduced ability to communicate is considered to be one of the most difficult aspects of the disease. 15 Acoustical voice analyses and measurement methods might provide useful biomarkers for the diagnosis of PD in the early stage of the disease, 22 for possible remote monitoring of patients, 23 but above all, for providing important feedback in voice treatment for clinicians or patients themselves.…”
Section: Introductionmentioning
confidence: 99%
“…5 LSVT has become well established as a behavioral treatment modality for voice and speech in PD 6 in randomized control trials, with demonstrated increases in overall loudness and other voice characteristics maintained as long as 2 years post-treatment. [7][8][9] However, studies of speech intelligibility before and after this treatment have been limited. Speech intelligibility has been described as both ''the behavioral standard of communication'' 10 (p. 1) and the primary goal of dysarthria management.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have reported improvement for a variety of measures of structural/functional impairment following LSVT that should yield better speech intelligibility as a result of treatment. 13 Such measures have included perceived voice attributes, 9,14 acoustic measures of intensity, and other phonatory and articulatory characteristics, 15,16 as well as laryngeal physiologic changes. 17,18 Despite this, there has been surprisingly little direct research on speech intelligibility before and after LSVT.…”
Section: Introductionmentioning
confidence: 99%